Optimizing sulfur fertilizer application rate for profitable maize production in the savanna agroecological zones of Northern Ghana. (15th July 2022) - Agyin-Birikorang, Sampson; Tindjina, Ignatius; Fugice, Job; Dauda, Haruna W.; Issahaku, Alhaji Rahman; Iddrissu, Mumuni; Singh, Upendra
Abstract: Although several studies have established the importance of sulfur (S) in increasing maize productivity in the savanna agroecological zones (AEZs) of northern Ghana, the economically optimum S application rate is still unknown. In a two-year study at eight locations across the AEZs, we determined the economically optimum S application rate for S-deficient soils. We compared eight S application rates, ranging from 0 to 70 kg ha −1 at 10 kg intervals, for optimal maize productivity and profitability. The study identified 30 kg S ha −1 as the minimum rate that resulted in a plant tissue S concentration above the critical level of 0.15%. Although increasing the S application rate resulted in increases in maize grain yield, application of S beyond a rate of 30 kg ha −1 resulted in increases in maize grain yield that were not statistically significant and leveled off at 50 kg S ha −1 . Application rates ≥50 kg ha −1 resulted in a high proportion of the applied S not taken up by the plant and, thus, subject to losses from the soil. Based on agro-input prices at the local level and the farm-gate prices of maize, the greatest potential profit resulting from S application was observed at 30 kg S ha −1, with a projected average maize yield of between ∼4.2 and 5.3 Mg ha −1, representing >90% of the observed yield with the highest S application rate of 70 kg ha −1 . Thus, we conclude that, for sustainable and profitable maize production in S-deficient soils of the savanna AEZs of northern Ghana, an S applications rate of 30 kg ha −1 is economically justified.